TECHNOLOGICAL APPROACH TO THE DESIGN OF INDEPENDENT LEARNING IN THE DISCIPLINE OF “INFORMATION TECHNOLOGIES IN EDUCATION” IN ORDER TO IMPROVE THE QUALITY OF EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Asadova Yulduz Ismatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In this article, the theoretical aspects of teaching in an online learning environment are discussed, in line with information technology programmers in education. It also presents a methodology for using electronic platforms to assist students in managing the independent study hours allocated to subjects within a modular credit system in higher education institutions. In addition, students can use these platforms during training sessions to master independent learning topics. Through this article, students can get advice and answers to their questions that can help them in organizing independent learning in different types of higher education settings.